Keanekaragaman dan Pola Sebaran Moluska (Gastropoda dan Bivalvia) yang Berasosiasi Pada Ekosistem Mangrove di Pesisir Selatan Lombok Timur - Wayan Pasek Eka Sedana Putra; Abdul Syukur; Didik Santoso (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Mangrove ecosystems have an important role in coastal areas. Mangroves have a function as a shelter, foraging for food, and breeding various aquatic biota. Damage to mangrove forests can cause the service of mangrove ecosystems to decrease, especially for mollusk life. Mollusks are one of the associated biotas of mangroves whose life is influenced by mangrove forests. Therefore, the purpose of this study was to determine the diversity of mollusks and the relationship between mollusk density and mangrove density in the mangrove ecosystem of the southern coast of East Lombok. A sampling of mollusks used the quadrate sampling method by purposive sampling by taking into account the mangrove species contained in the observation plot. The collected data were analyzed by diversity index, distribution pattern, association, and Pearson correlation coefficient. Then a simple linear regression analysis was performed with the independent variable (x) mangrove density and the dependent variable (y) mollusk density. The results of this study were the discovery of 22 species of mollusks consisting of 17 species of gastropods and five species of bivalves. The density of mollusks in the mangrove ecosystem of the southern coast of East Lombok is 44.50±2.63 ind./m2. The diversity index at the study site was classified as moderate, with a value ranging from 1.99 to 2.46. The distribution pattern of mollusks at the research site is clustered with an Id value > 1. There are eight mollusk species associated with three mangrove species from 22 mollusk species found. The linear regression equation y = 0.084x – 0.2963 with a Pearson correlation coefficient (r) 0.95 describes a strong relationship between the independent variable (x) mangrove density and the dependent variable (y) mollusk density. This study concludes that there is a significant relationship between mangrove density and mollusk density as indicated by F-hit(41.01) > F-table (7.70) and P-value (0.003) < (0.05).